Seleção de famílias de feijão baseada em caracteres agronômicos e da qualidade nutricional - Jost, Evandro (2011)
The common bean is a basic food of Brazilian diet, with great importance in many regions of the country because of economic and/or nutritional reasons. Genetic variability related to the grain yield, morphologic, phenologic and nutritional traits, and others, makes possible the use of genetic improvement and gain genetic can be maximized when adequate methodologies are used to obtain segregant populations and selection of lines. So, the purposes of this study were to evaluate the efficiency of the Genealogic and Single Seed Descent (SSD) methods in the obtained of segregating populations and evaluate direct selection, indirect selection, classical index (SMITH, 1936; HAZEL, 1943), base index (WILLIANS, 1962), parameter and weight free index (ELSTON, 1963), desired gains index (PESEK; BAKER, 1969), multiplicative index (SUBANDI et al., 1973) and rank summation index (MULAMBA; MOCK, 1978) in the identification of common bean families with higher grain yield, morphologic and phenologic desirable traits and higher calcium and iron contents in the seeds. For that, an amount of 272 families from F7 generation 136 families obtained by the Genealogic method with selection in segregant generations for grain yield, 136 families obtained by the SSD method, and 17 registered cultivars to be grown in Rio Grande do Sul state were evaluated in simple lattice model 17 x 17. Through the Genealogic method we obtained a higher number of families with high grain yield, early cycle and a lower general adaptation note (better adaptation). The SSD method was efficient by selection the higher grain yield, higher number of families with the lowest lodging grade (erect type), higher insertion height of first pod and higher calcium and iron contents in seeds. Correlations unfavorable to the interests of improvement were observed between the characters grain yield and height insertion of first pod and calcium and iron content in seeds. The classical index (SMITH, 1936; HAZEL, 1943), the base index (WILLIANS, 1962) and the multiplicative index (SUBANDI et al., 1973) can provide higher genetic progress common bean lines showing high similarity between the selected lines.